Effect of sensory adaptations for routine dental care in individuals with intellectual and developmental disabilities: A preliminary study. Issue 3 (3rd July 2019) - Potter, Cynthia N.; Wetzel, Jane L.; Learman, Kenneth E.
ABSTRACT: Background: This study examined whether a sensory adapted dental environment (SADE) diminished anxiety and agitation in adults with intellectual and developmental disability (IDD) when compared to a routine dental environment (RDE). Method: Agitated behaviours (frequency and duration) were video-taped and anxiety-related physiological measures recorded (heart rate [HR] and blood pressure [BP]) during dental treatment in RDE and 6 months later in SADE. An ICC2, k assessed the reliability of subject behaviours. The impact of treatment condition was compared with paired t -tests and ANCOVAs. Results: 41 participants, 22 males, aged 47.9 (14.2), were examined; 61% were diagnosed with profound IDD. SADE reduced frequency and duration of agitated behaviours and reduced physiological evidence of agitation (HR and BP) over RDE with p  < .004. Conclusion: This research demonstrated a decrease in frequency and duration of agitated behaviours and smaller changes in HR and BP when dental care is provided in a SADE.